Modification of Iraqi Asphalt 40/50 Properties Using Saw Dust (SD) and Natural Rubber Latex - Rusul l M. Darwesh (Al-Mustansiriyah Journal of Science)
The aim of this research is to enhance the fundamental properties for asphalt binder as those spec-ifications relate to performance of asphalt mixtures. In this paper studied the effect of add (2, 4 %) SD in different sizes and (3, 5 and 7%) Natural rubber latex to the straight asphalt 40/50 produced from Al-Dura refinery at 160C, it was added each additive separately and then added together to asphalt in same temperature, then tested physically and mechanically according to the American Society for Testing and Materials (ASTM), the result showed largely improvement.